Case Report: A chronic myeloid leukemia patient with e8a2 BCR::ABL1 fusion transcript was successfully treated with Flumatinib - Hao, Shanfeng; Zhang, Yao; Shao, Qing; Li, Lijuan (Frontiers in Oncology, 2025)
The majority of patients with chronic myeloid leukemia (CML) present with BCR::ABL1 transcripts involving the b2a2 (e13a2) and/or b3a2 (e14a2) junctions. However, a small subset of cases exhibit atypical breakpoints. These atypical BCR::ABL1 transcripts are found in approximately 2% of CML patients. It is essential to identify these atypical variants as they respond to tyrosine kinase inhibitor therapy, similar to patients with the more common transcript types. This report described a CML patient with a rare e8a2 BCR::ABL1 transcript variant, who also presented with difficult-to-correct iron-deficiency anemia. The patient was treated with Flumatinib and achieved complete hematologic remission at 1 month, complete cytogenetic remission at 3 months, and major molecular remission at 6 months.